A numerical model for the flow condensation of the binary zeotropic mixture. (January 2022) - Li, Ke; Liu, Yuce; Wen, Jian; Wang, Simin; Tu, Jiyuan
Abstract: Inspired by the quasi-static equilibrium state theory and the method of computational fluid dynamics, a mass and heat transfer model is proposed to simulate the condensation of the binary zeotropic mixtures. Combining the VOF method and species transport model, the mass transfer and heat transfer of the components in the liquid phase and vapor phase are analyzed, separately. The experiments of R32/R1234ze(E) and R134a/R1234ze(E) mixtures with different mass fluxes and mass compositions were chosen to validate this model. The results show the numerical data of heat transfer coefficients agree well with the experimental results. The condensation of R32/R1234ze(E) mixtures in mini-channels were simulated. The effects of mass flux, tube diameter and mass composition on the heat transfer coefficient, film thickness, velocity distribution, temperature distribution, and concentration distribution were investigated. The results show the mixture with more R32 has a larger HTC. The concentration of R32 vapor near the vapor-liquid interface increases with the decrease of vapor quality. And the mass flux has little effect on the concentration of R32 vapor.